Sodium ion positive electrode material, preparation method thereof and sodium ion battery
By using sintering aids mixed with sand grinding and ester organic compounds in the preparation of cathode materials for sodium ion batteries, the problem of low battery specific capacity of existing sodium iron pyrophosphate cathode materials has been solved, and high gram capacity and stable cycling have been achieved. high-performance cathode materials.
Patent Information
- Application Number
- CN202411232869.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-21
AI Technical Summary
The existing batteries made of sodium ferric pyrophosphate positive electrode material have low specific capacity and cannot exert their high capacity performance.
The initial raw materials and water are mixed and sanded to obtain emulsion A, which is then dried and sintered to prepare a carbon-coated sodium iron pyrophosphate cathode material. The method involves using ester organic compounds as carbon sources and sintering aids at high temperatures to promote sintering and generate a high-content NFPP phase.
The gram capacity of the positive electrode material is increased, allowing the battery to maintain stable discharge capacity during the cycle charging process, providing better reliability and endurance.
Smart Images

Figure CN119340356A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] At present, the mainstream positive electrode materials of sodium ion batteries mainly include layered oxides, Prussian blue analogs, and polyanions. Among them, transition metal oxides have a high compaction density and a high discharge capacity, but there are complex phase changes in the process of sodium insertion and extraction, which leads to structural collapse and serious performance degradation; Prussian blue and its analogs have high capacity and discharge voltage, but the lattice water in its structure is difficult to remove, and the charging and discharging process is prone to gasification, causing battery failure; and polyanion positive electrode materials have the characteristics of low cost and good cycle performance. The polyanion material is a framework structure composed of alkali metal ions, transition metal ions and anion groups connected to each other in the form of common points / lines / surfaces. Among them, Fe-based phosphate materials have broad application prospects due to their excellent structural stability and large resource abundance. Especially sodium iron pyrophosphate Na 4 Fe 3 (PO 4 ) 3 P 2 O 7 , with a higher theoretical capacity (129mAh / g), a higher discharge platform (3.1V vs Na / Na + ), but it also has obvious defects, such as low electronic conductivity and easy generation of impurities, which makes it difficult to fully utilize its capacity.
[0003] The existing patent publication number CN116565165A discloses a dual-continuous phase coated sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof, wherein the specific steps are: 1) preparing sodium iron phosphate pyrophosphate slurry: uniformly mixing a sodium source, an iron source, a phosphorus source and a solvent to obtain a sodium iron phosphate pyrophosphate slurry; 2) spray drying the sodium iron phosphate pyrophosphate slurry obtained in step 1) to obtain a sodium iron phosphate pyrophosphate precursor; 3) mixing the sodium iron phosphate pyrophosphate precursor obtained in step 2) with a carbon source, a titanium source and a niobium source, and then grinding the mixture; 4) sintering the sodium iron phosphate pyrophosphate precursor obtained in step 3) in a protective atmosphere, heating to 200-400°C at a rate of 1-10°C / min, keeping warm for 2-10 hours, then heating to 500-700°C at a rate of 1-10°C / min, keeping warm for 6-24 hours, and then cooling; the desired positive electrode material is obtained, and the obtained positive electrode material is made into a battery to measure the specific capacity and cycle performance, wherein the specific capacity is lower than 90mAh / g, and the high capacity performance of the sodium iron phosphate pyrophosphate cannot be exerted. Summary of the invention
[0004] The main purpose of the present invention is to provide a sodium ion positive electrode material and a preparation method thereof and a sodium ion battery, aiming to solve the technical problem that the specific capacity of the battery made of the existing sodium iron phosphate pyrophosphate positive electrode material is not high.
[0005] To achieve the above object, the present invention provides a method for preparing a sodium ion positive electrode material, the method comprising the following steps:
[0006] Step 1, mixing and sand-milling the initial raw materials and water to obtain an emulsion A, wherein the initial raw materials include a sodium source, an iron source, a phosphorus source and a carbon source, the mass ratio of the initial raw materials to water is (10-40):(60-90), the pH value of the emulsion A is 6-8, and the carbon source includes an ester organic matter or a mixture of an ester organic matter and at least one of glucose, sucrose, citric acid, stearic acid, oxalic acid, and cellulose;
[0007] Step 2, drying the emulsion A to obtain a precursor powder B;
[0008] Step 3, sintering the precursor powder B, and obtaining the sodium ion positive electrode material after natural cooling.
[0009] Optionally, in step 1, the sodium source includes at least one of metallic sodium, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium formate, sodium acetate, sodium sulfate, and sodium citrate.
[0010] Optionally, in step 1, the iron source includes at least one of iron oxide, ferric nitrate, ferric sulfate / ferrous sulfate, ferric acetate, ferric formate, ferrous oxalate, ferric / ferrous hydroxide, and ferric / ferrous phosphate.
[0011] Optionally, in step 1, the phosphorus source includes at least one of phosphoric acid, metaphosphoric acid, sodium metaphosphate, sodium phosphate, sodium dihydrogen phosphate / lithium, disodium hydrogen phosphate / lithium, ammonium dihydrogen phosphate, ferric phosphate, pyrophosphoric acid, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.
[0012] Optionally, in step 1, the ester organic matter includes at least one of dimethyl malonate, ethyl 2-butynoate, propargyl propionate, dimethyl malonate, allyl hexanoate, ethyl acetate, propylene carbonate, methyl p-hydroxybenzoate, ethyl pyruvate, trimethyl orthoformate, isopentyl butyrate, ethyl acrylate, and cationic ester compounds.
[0013] Optionally, in step 1, the mixed sand grinding treatment refers to coarse grinding the mixture of the initial raw material and water using zirconium balls with a particle size of 0.5-1 mm, and then fine grinding using zirconium balls with a particle size of 0.1-0.2 mm, and the weight ratio of zirconium beads to insoluble matter in the coarse grinding and fine grinding is 3:1-15:1.
[0014] Optionally, in step 2, the drying process includes one of spray drying, oil bath drying, water bath drying and flash drying.
[0015] Optionally, in step 3, inert gas protection is introduced in advance, and the temperature is increased to 350° C. at a heating rate of 1° C. / min and kept at this temperature for 4 hours, and then the temperature is increased to 500-650° C. at a heating rate of 5° C. / min and kept at this temperature for 10-15 hours;
[0016] Alternatively, the temperature is directly increased to 500-650°C at a heating rate of 2-4°C / min and sintered at this temperature for 15-20 hours.
[0017] In addition, in order to achieve the above object, the present invention also provides a sodium ion positive electrode material, which is prepared according to the preparation method of the sodium ion positive electrode material described above, wherein the sodium ion positive electrode material is carbon-coated sodium iron phosphate pyrophosphate, and the chemical formula of the sodium iron phosphate pyrophosphate is Na 4 Fe 3 (PO 4 ) 3 P 2 O 7 .
[0018] In addition, in order to achieve the above-mentioned purpose, the present invention also provides a sodium ion battery, which includes the above-mentioned sodium ion positive electrode material.
[0019] Beneficial effects:
[0020] The ester carbon source used in the present invention can not only reduce trivalent Fe, but also carbon-coat the particles. It decomposes and produces acid during the high-temperature sintering process. The acid can corrode the internal particles, reduce the sintering activation energy, and promote sintering. + You can also contact PO 4 3- The O atoms in the 2 O 7 4- The formation of NFPP phase (orthorhombic system Pn21a space group) is increased, and the gram capacity of the obtained material is increased, thereby providing better reliable power and endurance for subsequent battery applications. The principle is that ester organic matter decomposes into carboxylic acid and olefin at high temperature. Due to its acidity, carboxylic acid can corrode the precursor particles during the sintering process, reduce the sintering energy barrier, and thus promote sintering. At the same time, H in the acidic environment + Easier and PO 4 3- O released in 2- Combined to generate H 2 O, more conducive to promoting P 2 O 7 4- Generation of (2H+ +2PO 4 3- →H 2 O+P 2 O 7 4- ), thereby reducing the inactive phase NaFePO 4 The generation of esters is beneficial to the improvement of material capacity; and the decomposition products of esters, carboxylic acids and olefins, can be used as reducing carbon sources and coating carbon sources. Conventional acidic organic substances (such as citric acid) usually have a low melting point and high viscosity, which leads to serious adhesion of powders to the wall during spray drying and inability to collect materials normally. In addition, acidic organic carbon sources can also cause the slurry to form a sol, making spraying difficult. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic flow chart of an embodiment of a method for preparing a sodium ion positive electrode material according to the present invention;
[0022] Figure 2 is the XRD pattern of the positive electrode material prepared in Example 1;
[0023] Figure 3 is a SEM image of the positive electrode material prepared in Example 1;
[0024] Figure 4 is the discharge specific capacity of the battery made using the positive electrode material in Example 1;
[0025] Figure 5 is a SEM image of the positive electrode material prepared in Example 2;
[0026] Figure 6 is a SEM image of the positive electrode material prepared in Example 3;
[0027] Figure 7 is a SEM image of the positive electrode material prepared in Example 4;
[0028] Figure 8 is a SEM image of the positive electrode material prepared in Comparative Example 1;
[0029] Fig. 9 is a SEM image of the positive electrode material prepared in Comparative Example 2;
[0030] Fig.10 This is the SEM image of the positive electrode material prepared in Comparative Example 3.
[0031] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0032] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0033] like Figure 1 As shown, the present invention provides an embodiment of a method for preparing a sodium ion positive electrode material, the method comprising the following steps:
[0034] Step 1, mixing and sand-milling the initial raw materials and water to obtain an emulsion A, wherein the initial raw materials include a sodium source, an iron source, a phosphorus source and a carbon source, the mass ratio of the initial raw materials to water is (10-40): (60-90), the pH value of the emulsion A is 6-8, and the carbon source includes an ester organic matter or a mixture of an ester organic matter and at least one of glucose, sucrose, citric acid, stearic acid, oxalic acid and cellulose; the mixed sand-milling treatment refers to firstly coarse-milling the mixture of the initial raw materials and water using a zirconium ball with a particle size of 0.5-1 mm, and controlling the coarse-milled particle size D50 to be between 0.9-2 um, and then fine-milling using a zirconium ball with a particle size of 0.1-0.2 mm, and the fine-milled particle size target is D50 within 50-100 nm and D90 within 300 nm. The particle interface energy in this particle size range is relatively large. Under subsequent high temperature conditions, the instability of the interface elements will cause the particles to fuse with each other, increase the mixing degree between ions, and be beneficial to material nucleation. It can be seen that the above-mentioned mixed sand milling achieves the effect of particle pulverization, crushing or atomic splitting in the form of shear force, gravity and friction force, and realizes nano-sizing of insoluble matter, making it close to the ionic form and merging with soluble ions to ensure the uniformity of dispersion of elements in the slurry.
[0035] Preferably, the weight ratio of zirconium beads to insoluble matter in the above-mentioned rough grinding and fine grinding is 3:1-15:1. The rough grinding time is 0.5h-3h, the rotation speed is 300-1000rpm; the fine grinding time is 0.5h-3h, and the rotation speed is 2000-3000rpm.
[0036] Preferably, the molar ratio of Na, Fe and P in the sodium source, iron source and phosphorus source is (3.5-4.5): (2.5-3.5): (3.5-4.5).
[0037] Preferably, the mass of the carbon source is 5-30% of the theoretical mass fraction of the product.
[0038] Furthermore, the sodium source includes at least one of metallic sodium, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium formate, sodium acetate, sodium sulfate, and sodium citrate.
[0039] Furthermore, the iron source includes at least one of iron oxide, ferric nitrate, ferric sulfate / ferrous sulfate, ferric acetate, ferric formate, ferrous oxalate, ferric / ferrous hydroxide, and ferric / ferrous phosphate.
[0040] Furthermore, the phosphorus source includes at least one of phosphoric acid, metaphosphoric acid, sodium metaphosphate, sodium phosphate, sodium dihydrogen phosphate / lithium, disodium hydrogen phosphate / lithium, ammonium dihydrogen phosphate, iron phosphate, pyrophosphoric acid, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.
[0041] Further, the ester organic matter includes at least one of dimethyl malonate, ethyl 2-butynoate, propargyl propionate, dimethyl malonate, allyl caproate, ethyl acetate, propylene carbonate, methyl p-hydroxybenzoate, ethyl pyruvate, trimethyl orthoformate, isopentyl butyrate, ethyl acrylate, and cationic ester compounds. Preferably, the ester carbon source is preferably a monomer with a relatively low molecular weight and is easier to break at high temperature, and the relative molecular weight does not exceed 500.
[0042] Step 2, drying the emulsion A to obtain a precursor powder B; wherein the drying treatment includes one of spray drying, oil bath drying, water bath drying and flash drying. Preferably, when spray drying is adopted, the inlet air temperature is controlled to be ≥260°C, and the outlet temperature is between 100-110°C, and the water content of the obtained spherical precursor dry powder is less than 3%. The principle is that when the inlet air temperature is higher than 260°C, the water in the droplets can evaporate quickly, and at the same time, a uniform sphere is formed under the action of the surface tension of the droplets. When the water content in the dry powder is lower than 3%, the surface of the spherical precursor dry powder is not easy to adhere to each other, and the fluidity is good.
[0043] Step 3, sintering the precursor powder B, and obtaining the sodium ion positive electrode material after natural cooling. Specifically, the sintering process is carried out under the protection of an inert gas, and can be sintered in stages, or directly heated to a preset temperature for sintering. The inert gas is an inert gas such as nitrogen, argon or helium, and the oxygen content in the sintering furnace is controlled to be less than 50 ppm.
[0044] Preferably, staged sintering refers to heating the temperature to 350°C at a heating rate of 1°C / min and sintering at this temperature for 4 hours, then heating the temperature to 500-650°C at a heating rate of 5°C / min and sintering at this temperature for 10-15 hours to ensure sufficient crystal growth of the material; and direct sintering refers to directly heating the temperature to 500-650°C at a heating rate of 2-4°C / min and sintering at this temperature for 15-20 hours.
[0045] The final sodium ion positive electrode material is carbon-coated sodium iron phosphate pyrophosphate, wherein the carbon content is 0.3-6% of the mass fraction of the final sodium ion positive electrode material, and the chemical formula of the sodium iron phosphate pyrophosphate is Na 4 Fe 3 (PO 4 ) 3 P 2 O 7The principle is that ester organic matter decomposes into carboxylic acid and olefin at high temperature. Due to its acidity, carboxylic acid can corrode the precursor particles during the sintering process, reduce the sintering energy barrier, and thus promote sintering. At the same time, H + Easier and PO 4 3- O released in 2- Combined to generate H 2 O, more conducive to promoting P 2 O 7 4- Generation of (2H + +2PO 4 3- →H 2 O+P 2 O 7 4- ), thereby reducing the inactive phase NaFePO 4 The generation of trivalent Fe is beneficial to the improvement of material capacity; on the other hand, the decomposition products of ester, carboxylic acid and olefin, can be used as reducing carbon sources and coating carbon sources. Conventional acidic organic substances (such as citric acid) usually have a low melting point and a high viscosity, which leads to serious adhesion of the powder to the wall during spray drying and inability to collect materials normally. Sometimes, acidic organic carbon sources can also cause the slurry to form a sol, resulting in difficulty in spraying. Therefore, the ester carbon source used in the present invention can not only achieve the reduction of trivalent Fe, but also carbon-coat the particles. It decomposes and produces acid during the high-temperature sintering process. The acid can corrode the internal particles, reduce the sintering activation energy, and promote sintering. + You can also contact PO 4 3- The O atoms in the 2 O 7 4- The formation of NFPP phase (orthorhombic system Pn21a space group) is increased. In addition, when using cationic ester compounds, such as tetrabutyl titanate, titanium ions can be used as doping elements to enter the material lattice, and esters can be used as carbon sources and sintering aids.
[0046] In addition, the present invention also provides a sodium ion battery, which includes the above-mentioned sodium ion positive electrode material.
[0047] Furthermore, in order to better illustrate the performance of the positive electrode material and the battery made of the positive electrode material in the present invention, the following is an explanation through specific embodiments.
[0048] Example 1
[0049] Step 1: Add water, sodium carbonate, iron phosphate, ammonium dihydrogen phosphate and ethyl acetate to the coarse grinding tank in proportion, wherein the amount of ethyl acetate is 10% of the theoretical weight of the product. The speed of the coarse ball mill is set to 500 rpm, the mass ratio of zirconia balls to insoluble matter is 10:1, the particle size of the zirconia balls is 0.5 mm, and the ball milling time is 1 hour. Then transfer to the fine grinding equipment, the speed is set to 2800 rpm, the ball milling time is 40 minutes, and an emulsion slurry is obtained.
[0050] Step 2: spray-dry the slurry obtained in step 1, with the inlet air temperature at 260° C. and the outlet air temperature at 110° C., to obtain a precursor powder uniformly mixed with iron, sodium and anion groups.
[0051] Step 3: Sinter the precursor powder obtained in step 2 at a heating rate of 1°C / min to 350°C for 4 hours, then at a heating rate of 5°C / min to 500°C for 10 hours, and then cool naturally to obtain carbon-coated nano-scale sodium iron phosphate pyrophosphate. The obtained product is subjected to XRD test, and the obtained XRD spectrum is as follows: Figure 2 As shown, the crystal structure was shown to belong to the Pn21a space group, where The parameters are close to those in the crystal structure literature, and the NFPP ratio is further calculated in the jade software through XRD data, where the NFPP phase accounts for 78.4%, the m-NFP phase accounts for 4.6%, and the NFP2 phase accounts for 17%; and further SEM tests are performed, such as Figure 3 As shown in the figure, the large particles are stacked together by small primary particles, and the particle size of each primary particle is at the nanometer level.
[0052] Example 2
[0053] Step 1: Add water, sodium carbonate, iron phosphate, ammonium dihydrogen phosphate and propylene carbonate to the coarse grinding tank in proportion, wherein the amount of propylene carbonate is 10% of the theoretical weight of the product. The speed of the coarse ball mill is set to 500 rpm, the mass ratio of zirconium oxide balls to insoluble matter is 10:1, the particle size of the zirconium oxide balls is 0.5 mm, and the ball milling time is 1 hour. Then transfer to the fine grinding equipment, the speed is set to 2800 rpm, the ball milling time is 40 minutes, and an emulsion slurry is obtained.
[0054] Step 2: spray-dry the slurry obtained in step 1, with the inlet air temperature at 260° C. and the outlet air temperature at 110° C., to obtain a precursor powder uniformly mixed with iron, sodium and anion groups.
[0055] Step 3: Sinter the precursor powder obtained in step 2 at a heating rate of 1°C / min to 350°C for 4h, then at a heating rate of 5°C / min to 550°C for 15h, and then naturally cool to obtain carbon-coated nano-scale sodium iron phosphate pyrophosphate, and perform SEM test, as shown in FIG. Figure 5 As shown in the figure, the large particles are composed of small primary particles stacked together, and the particle size of each primary particle is at the nanoscale, and the final NFPP phase accounts for 79.6%, the m-NFP phase accounts for 3.8%, and the NFP2 phase accounts for 16.8%.
[0056] Example 3
[0057] Step 1: Add water, sodium carbonate, iron phosphate, ammonium dihydrogen phosphate and allyl caproate in a coarse grinding tank in proportion, wherein the amount of allyl caproate is 10% of the theoretical weight of the product. The speed of the coarse ball mill is set to 500 rpm, the mass ratio of zirconium oxide balls to insoluble matter is 10:1, the particle size of the zirconium oxide balls is 0.5 mm, and the ball milling time is 1 hour. Then transfer to the fine grinding equipment, the speed is set to 2800 rpm, the ball milling time is 40 minutes, and an emulsion slurry is obtained.
[0058] Step 2: spray-dry the slurry obtained in step 1, with the inlet air temperature at 260° C. and the outlet air temperature at 110° C., to obtain a precursor powder uniformly mixed with iron, sodium and anion groups.
[0059] Step 3: Sinter the precursor powder obtained in step 2 at a heating rate of 2°C / min to 600°C, keep the temperature for 15 hours, and then cool naturally to obtain carbon-coated nano-scale sodium iron phosphate pyrophosphate, and perform SEM test. Figure 6 As shown in the figure, the large particles are composed of small primary particles stacked together, and the particle size of each primary particle is at the nanoscale, and the final NFPP phase accounts for 78.9%, the m-NFP phase accounts for 4.2%, and the NFP2 phase accounts for 16.9%.
[0060] Example 4
[0061] Step 1: Add water, ferrous oxalate, ferric phosphate, sodium pyrophosphate and ethyl acetate to the coarse grinding tank in proportion, wherein the amount of ethyl acetate is 10% of the theoretical weight of the product. The speed of the coarse ball mill is set to 500 rpm, the mass ratio of zirconia balls to insoluble matter is 10:1, the particle size of the zirconia balls is 0.5 mm, and the ball milling time is 1 hour. Then transfer to the fine grinding equipment, the speed is set to 2800 rpm, the ball milling time is 40 minutes, and an emulsion slurry is obtained.
[0062] Step 2: spray-dry the slurry obtained in step 1, with the inlet air temperature at 260° C. and the outlet air temperature at 110° C., to obtain a precursor powder uniformly mixed with iron, sodium and anion groups.
[0063] Step 3: Sinter the precursor powder obtained in step 2 at a heating rate of 4°C / min to 650°C, keep the temperature for 15 hours, and then cool naturally to obtain carbon-coated nano-scale sodium iron phosphate pyrophosphate, and perform SEM test. Figure 7 As shown in the figure, the large particles are composed of small primary particles stacked together, and the particle size of each primary particle is at the nanoscale, and the final NFPP phase accounts for 76.5%, the m-NFP phase accounts for 5.4%, and the NFP2 phase accounts for 18.1%.
[0064] Comparative Example 1
[0065] Step 1: Add water, sodium carbonate, iron phosphate, ammonium dihydrogen phosphate and glucose to the coarse grinding tank in proportion, wherein the amount of glucose is 10% of the theoretical weight of the product. The speed of the coarse ball mill is set to 500 rpm, the mass ratio of zirconium oxide balls to insoluble matter is 10:1, the particle size of the zirconium oxide balls is 0.5 mm, and the ball milling time is 1 hour. Then transfer to the fine grinding equipment, the speed is set to 2800 rpm, the ball milling time is 40 minutes, and an emulsion slurry is obtained.
[0066] Step 2: spray-dry the slurry obtained in step 1, with the inlet air temperature at 260° C. and the outlet air temperature at 110° C., to obtain a precursor powder uniformly mixed with iron, sodium and anion groups.
[0067] Step 3: Sinter the precursor powder obtained in step 2 at a heating rate of 1°C / min to 350°C for 4h, then at a heating rate of 5°C / min to 550°C for 10h, and then naturally cool to obtain sodium iron pyrophosphate, and perform SEM test. Figure 8 As shown, although it can be seen from the figure that the particle size of a single primary particle is at the nanometer level, the final NFPP phase accounts for 74.2%, the m-NFP phase accounts for 12.2%, and the NFP2 phase accounts for 13.6%.
[0068] Comparative Example 2
[0069] Step 1: Add water, sodium carbonate, ferric phosphate, ammonium dihydrogen phosphate and citric acid in a coarse grinding tank in proportion, wherein the amount of citric acid is 10% of the theoretical weight of the product. The speed of the coarse ball mill is set to 500 rpm, the mass ratio of zirconia balls to insoluble matter is 10:1, the particle size of the zirconia balls is 0.5 mm, and the ball milling time is 1 hour. Then transfer to the fine grinding equipment, the speed is set to 2800 rpm, the ball milling time is 40 minutes, and an emulsion slurry is obtained.
[0070] Step 2: spray-dry the slurry obtained in step 1, with the inlet air temperature at 260° C. and the outlet air temperature at 110° C., to obtain a precursor powder uniformly mixed with iron, sodium and anion groups.
[0071] Step 3: Sinter the precursor powder obtained in step 2 at a heating rate of 4°C / min to 550°C, keep the temperature for 15 hours, and then cool naturally to obtain sodium iron pyrophosphate, and perform SEM test. Fig. 9 As shown, although it can be seen from the figure that the particle size of a single primary particle is at the nanometer level, the final NFPP phase accounts for 73.8%, the m-NFP phase accounts for 13.6%, and the NFP2 phase accounts for 12.6%.
[0072] Comparative Example 3
[0073] Step 1: Add water, sodium carbonate, iron phosphate, ammonium dihydrogen phosphate and vitamin C in a coarse grinding tank in proportion, wherein the amount of vitamin C is 10% of the theoretical weight of the product. The speed of the coarse ball mill is set to 500 rpm, the mass ratio of zirconium oxide balls to insoluble matter is 10:1, the particle size of the zirconium oxide balls is 0.5 mm, and the ball milling time is 1 hour. Then transfer to the fine grinding equipment, the speed is set to 2800 rpm, the ball milling time is 40 minutes, and an emulsion slurry is obtained.
[0074] Step 2: spray-dry the slurry obtained in step 1, with the inlet air temperature at 260° C. and the outlet air temperature at 110° C., to obtain a precursor powder uniformly mixed with iron, sodium and anion groups.
[0075] Step 3: Sinter the precursor powder obtained in step 2 at a heating rate of 1°C / min to 350°C for 4h, then at a heating rate of 5°C / min to 650°C for 15h, and then naturally cool to obtain sodium iron pyrophosphate, and perform SEM test. Fig.10 As shown, although it can be seen from the figure that the particle size of a single primary particle is at the nanometer level, the final NFPP phase accounts for 72.6%, the m-NFP phase accounts for 11.5%, and the NFP2 phase accounts for 15.9%.
[0076] Based on the above embodiments and comparative examples, the selection of components in the embodiments and comparative examples described in Table 1 is summarized.
[0077] Table 1 - Selection of components in examples and comparative examples
[0078] Recipe variables Example 1 Sodium carbonate, ferric phosphate, diammonium phosphate, ethyl acetate Example 2 Sodium carbonate, ferric phosphate, diammonium phosphate, propylene carbonate Example 3 Sodium carbonate, ferric phosphate, diammonium phosphate, allyl hexanoate Example 4 Ferrous oxalate, ferric phosphate, sodium pyrophosphate, ethyl acetate Comparative Example 1 Sodium carbonate, ferric phosphate, diammonium phosphate, glucose Comparative Example 2 Sodium carbonate, ferric phosphate, diammonium phosphate, citric acid Comparative Example 3 Sodium carbonate, ferrous phosphate, diammonium phosphate, vitamin C
[0079] Performance testing:
[0080] The gram capacities of the embodiments and comparative examples were measured using a button cell test.
[0081] The specific preparation and testing methods of button cells are as follows:
[0082] NMP was used as a solvent, and a slurry with a solid content of 60% was prepared according to the ratio of active material: SP: PVDF = 80:10:10, which was evenly coated on an aluminum foil to prepare a positive electrode.
[0083] A metallic sodium sheet with a diameter of 14 mm was used as the negative electrode, and 1 mol LiFP6 (EC:DMC:EMC=1:1:1, V / V) was used as the electrolyte. The battery was packaged in the order of negative electrode shell-spring-gasket-sodium sheet-electrolyte-diaphragm-positive electrode sheet-gasket-positive electrode shell. The whole process was completed in a glove box filled with argon.
[0084] The electrical performance test was carried out at a test temperature of 25°C. The battery capacity test method was: charging with a constant current and constant voltage charging method, with a termination voltage of 4.0V; discharging with a constant current discharge method, with a discharge cut-off voltage of 1.7V. The test results are shown in Table 2.
[0085] Table 2 - Component ratio of NFPP+NFP2 in the examples and comparative examples and 0.1C discharge capacity in grams
[0086]
[0087] It can be seen from Table 2 above that the 0.1C discharge capacity of the positive electrode materials in Examples 1-4 is basically maintained above 100mAh / g, which is greater than the batteries made from the positive electrode materials in the comparative examples, and the corresponding NFPP+NFP2 content (%) in the examples is above 90%. It can be seen that the NFPP+NFP2 content of the positive electrode materials prepared by the above preparation method of the present invention is greater than the corresponding NFPP+NFP2 content in comparative examples 1-3. The principle is that the increase in the active phase NFPP will inhibit the increase in the content of the impurity phase, thereby increasing the charge and discharge capacity of the material. And in the case of Figure 4 It can be seen from the discharge specific capacity shown that at a discharge capacity of 0.1C, after 40 discharges, the discharge capacity of the battery can still remain unchanged from the initial state, and the batteries prepared by implementations 2-4 have the same effect as in Example 1. It can be seen that the positive electrode material prepared by the above-mentioned preparation method of the present invention can improve the specific capacity of the battery and has little fluctuation after a certain number of cycles of charging, and thus the stable battery performance can ensure that the battery can provide reliable power and endurance when used in corresponding tools and equipment.
[0088] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or system. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or system including the element.
[0089] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0090] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a sodium ion positive electrode material, characterized in that: The method comprises the following steps: Step 1, mixing and sand-milling the initial raw materials and water to obtain an emulsion A, wherein the initial raw materials include a sodium source, an iron source, a phosphorus source and a carbon source, the mass ratio of the initial raw materials to water is (10-40):(60-90), the pH value of the emulsion A is 6-8, and the carbon source includes an ester organic matter or a mixture of an ester organic matter and at least one of glucose, sucrose, citric acid, stearic acid, oxalic acid, and cellulose; Step 2, drying the emulsion A to obtain a precursor powder B; Step 3, sintering the precursor powder B, and obtaining the sodium ion positive electrode material after natural cooling.
2. The method for preparing the sodium ion positive electrode material according to claim 1, characterized in that: In step 1, the sodium source includes at least one of metallic sodium, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium formate, sodium acetate, sodium sulfate, and sodium citrate.
3. The method for preparing the sodium ion positive electrode material according to claim 1, characterized in that: In step 1, the iron source includes at least one of iron oxide, ferric nitrate, ferric sulfate / ferrous sulfate, ferric acetate, ferric formate, ferrous oxalate, ferric / ferrous hydroxide, and ferric / ferrous phosphate.
4. The method for preparing the sodium ion positive electrode material according to claim 1, characterized in that: In step 1, the phosphorus source includes at least one of phosphoric acid, metaphosphoric acid, sodium metaphosphate, sodium phosphate, sodium dihydrogen phosphate / lithium, disodium hydrogen phosphate / lithium, ammonium dihydrogen phosphate, ferric phosphate, pyrophosphoric acid, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.
5. The method for preparing the sodium ion positive electrode material according to claim 1, characterized in that: In step 1, the ester organic matter includes at least one of dimethyl malonate, ethyl 2-butynoate, propargyl propionate, dimethyl malonate, allyl hexanoate, ethyl acetate, propylene carbonate, methyl p-hydroxybenzoate, ethyl pyruvate, trimethyl orthoformate, isopentyl butyrate, ethyl acrylate, and cationic ester compounds.
6. The method for preparing the sodium ion positive electrode material according to claim 1, characterized in that: In step 1, the mixed sand grinding treatment means that the mixture of the initial raw material and water is first coarsely ground using zirconium balls with a particle size of 0.5-1 mm, and then finely ground using zirconium balls with a particle size of 0.1-0.2 mm, and the weight ratio of zirconium beads to insoluble matter in the coarse grinding and fine grinding is 3:1-15:
1.
7. The method for preparing a sodium ion positive electrode material according to any one of claims 1 to 6, characterized in that: In step 2, the drying process includes one of spray drying, oil bath drying, water bath drying and flash drying.
8. The method for preparing a sodium ion positive electrode material according to claim 7, characterized in that: In step 3, inert gas protection is introduced in advance, and the temperature is increased to 350°C at a heating rate of 1°C / min and kept at this temperature for 4 hours, and then the temperature is increased to 500-650°C at a heating rate of 5°C / min and kept at this temperature for 10-15 hours; Alternatively, the temperature is directly increased to 500-650°C at a heating rate of 2-4°C / min and sintered at this temperature for 15-20 hours.
9. A sodium ion positive electrode material, characterized in that: The method for preparing a sodium ion positive electrode material according to any one of claims 1 to 8, wherein the sodium ion positive electrode material is carbon-coated sodium iron phosphate pyrophosphate, and the chemical formula of the sodium iron phosphate pyrophosphate is Na4Fe3(PO4)3P2O7.
10. A sodium ion battery, characterized in that: The battery comprises the sodium ion positive electrode material according to claim 9.
Citation Information
Patent Citations
Bicontinuous phase coated ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN116565165A